PENGENDALIAN PIUTANG DAGANG UNTUK MENINGKATKAN EFEKTIF DAN EFISIENSI PENERIMAAN KAS PADA PT TIMUR JAYA INDOSTEEL - Oktaviani, Krismia; Tumewu, James (JURNAL LENTERA AKUNTANSI, 2023)
Accounts receivable is a concept in finance that refers to the amount owed to an entity (such as a company or individual) by another party who has received goods or services without paying in cash. This creates a financial liability for the debtor and a financial asset for the party providing the goods or services. Receivables management is a key element in effective financial management, which includes monitoring, controlling and collecting receivables to ensure good liquidity and business continuity. The aim of this research is to analyze how companies manage receivables so that delays in receivable payments can be minimized. The method used in this research is a qualitative method. The findings of this research are that companies have not strictly enforced fines for late debts owed to partners, even though delinquent receivables are money that still has to be paid to the company by partners whose payment due date has passed. Keywords: Effectiveness, Efficiency, Accounts Receivable